2012
DOI: 10.1164/rccm.201102-0273ci
|View full text |Cite
|
Sign up to set email alerts
|

Sedation and Analgesia in the Mechanically Ventilated Patient

Abstract: Sedation and analgesia are important components of care for the mechanically ventilated patient in the intensive care unit (ICU). An understanding of commonly used medications is essential to formulate a sedation plan for individual patients. The specific physiological changes that a critically ill patient undergoes can have direct effects on the pharmacology of drugs, potentially leading to interpatient differences in response. Objective assessments of pain, sedation, and agitation have been validated for use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 156 publications
1
123
1
2
Order By: Relevance
“…Positive endexpiratory pressure (PEEP) was adjusted by FiO 2 to meet the PaO 2 ≥55 mmHg or oxygen saturation of pulse oximetry (SpO 2 ) ≥88% (3,20). On the basis of analgesia by fentanyl, we sedated the patients with midazolam and/or propofol to meet the goal of Richmond Agitation-Sedation Scale between −2 and −4 (21). Additional treatment strategies such as organ function support, circulation stabilization, nutrition and internal environment maintenance were implemented in accordance with corresponding guidelines.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Positive endexpiratory pressure (PEEP) was adjusted by FiO 2 to meet the PaO 2 ≥55 mmHg or oxygen saturation of pulse oximetry (SpO 2 ) ≥88% (3,20). On the basis of analgesia by fentanyl, we sedated the patients with midazolam and/or propofol to meet the goal of Richmond Agitation-Sedation Scale between −2 and −4 (21). Additional treatment strategies such as organ function support, circulation stabilization, nutrition and internal environment maintenance were implemented in accordance with corresponding guidelines.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…[20][21][22] because of these considerations, evaluating communication between ICU nurses and on-call ICU physicians at night about patients' pain, agitation, and delirium provides a good focus for estimating the overall quality of ICU nurse-physician communication at night.…”
Section: Pharmacology In Critical Carementioning
confidence: 99%
“…Numerous studies have demonstrated that propofol, an intravenous anaesthetic widely used for general anaesthesia in ECT probably reduces adverse effects of ECT on memory and cognitive function 67and 68 .Propofol is an intravenous anaesthetic that is metabolized quickly hence leading to early awakening. It's a short-acting lipophilic drug that quickly crosses the blood-brain barrier with an onset of action ranging from seconds to minutes 69 . Butterfield et al also reported greater reduction in post ECT cognitive impairment with propofol compared with thiopental when assessing cognitive states 5 minutes after each ECT by applying various neuropsychological tests, including immediate and delay verbal memory 67 , confirming that propofolanaesthesia is less damaging to cognitive function when compared to older anesthetic agents such as thiopental.…”
Section: Prevention Of Neurocognitive Side-effect Of Electroconvumentioning
confidence: 99%